The effect of value added intellectual coefficient, firm size, and leverage on business performance in the ASEAN-5 service industry - Chen, Jessica Maris H. (Animo Repository, 2021)
This research is a causal-explanatory study that seeks to understand the cause-and-effect relationship between intellectual capital (IC) and business performance. Over the years, intellectual capital has been acknowledged as a critical driver for increasing firm value. However, there are still those who are unaware of its potential as a value creating asset due to difficulties in measurement and the traditional mindset of firms focusing more on tangible assets. The purpose of this paper is to obtain a clearer understanding of the cause-and-effect relationship between intellectual capital and business performance by focusing on a sector that is highly dependent on value adding assets. The study employs the extended Value Added Intellectual Coefficient (VAIC) model utilized by Bayraktaroglu, Calisir, and Baskak (2019) to quantify intangible assets. Performance measurements were then analyzed to identify their impact on business performance. The paper focuses on four components of the extended VAIC model namely, capital employed efficiency (CEE), human capital efficiency (HCE), relational capital efficiency (RCE) or customer capital efficiency (CCE), and structural capital efficiency (SCE) which includes innovation capital (RDE) as a subcomponent in its computation. This study applies the revenue per employee (RE), market to book ratio (MB), and return on equity (ROE) as the most suitable measurements of business performance in terms of productivity, market performance, and profitability, respectively. To gather the information needed, the researchers make use of the financial statements of publicly listed firms from the ASEAN-5, namely, Indonesia, Malaysia, Philippines, Singapore, and Thailand taken from the comprehensive database, Thomson Reuters. Through multiple linear regression analysis, the data derived is analyzed to determine the cause-and-effect relationship between the independent and dependent variables. The results of the study conclude that at least one component of VAIC has a significant effect on business performance. In terms of market value, CEE, SCE, and CCE were shown to have a positive and significant effect on MB while findings suggest that CEE and SCE have a positively significant and negatively significant effect on ROE, respectively. Moreover, firm size and leverage were found to not have significant effects on MB and ROE. This implies that service companies in the ASEAN-5 may utilize intellectual capital in value creation in order to obtain a competitive advantage in the market.